Temporal aspects of coach behaviour - Harry, L.; O'Donoghue, P. (World Congress of Performance Analysis of Sport IX, 2012)
The Arizona State University Observation Instrument (ASUOI) has been used in research into coach bevaviour for over 25 years (Lacy and Darst, 1984). The ASUOI allows the frequency, duration and intensity of 14 named coaching behaviours to be determined. However, these descriptive results do not include important details of temporal patterns in coach behaviour. Therefore, the purpose of the current investigation was to analyse data gathered using a computerized implementation of the ASUOI with respect to temporal patterns. The computerized system was implemented in Focus X2 (Elite Sports Analysis, Delgaty Bay, Fife, Scotland, UK) and applied to a netball coach who was observed during 4 coaching sessions for a total of 3 hours 30 minutes. The system had a good level of inter-observer reliability. A chi square test of independence was used to determine whether coaching bevaviour was independent of the previous coach behavior performed. It was necessary to use a subset of behaviours from the ASUOI in order to satisfy the assumptions of the chi square test as shown in Table 1. There was a significant influence of previous behavior on the behavior of the coach (.225 = 184.7, p < 0.001) with four behaviours followed by further instances of those behaviours more than expected (concurrent instruction, praise, pre-instruction and questioning). Other temporal patterns were that pre-instruction was followed by management, concurrent instruction was followed by praise and management was followed by pre-instruction more than expected. In addition to this quantitative analysis of coaching behaviours at the event level, qualitative analysis of video sequences revealed that there was a broad temporal structure to the training sessions. This type of analysis for coaching data in other sports may reveal chains of pairs of behaviours as well as cycles of behaviours. This additional information is an enhancement to the ASUOI which to date has been limited to a static analysis of behavior.